Marketing Mix Compenents of BreadTalk Company at Megamall Manado - Melisa S Sakul (COCOS, 2012)
Melisa Sakul. â€œMarketing Mix Compenents of BreadTalk Company at Megamall Manadoâ€. Under guidance of Ventje V. Rantung as chairman andÂ  Charles R. Ngangi and Yolanda P.I. Rori as members. The objective of this research is to determine the marketing mix competens of breadtalk company at megamall manado.The research was conducted in Manado from July to September 2012.Data is obtained from primary and secondary data. The primary data is obtained from interviews using questionnaires to consumers, while the secondary data obtained from interviews with the BreadTalk manager.The number of samples used in this researchwre 30 respondents.Methods of data analysis used in this research is descriptive to determine the marketing mix used by the company. The results shows that offering of products was very variedthe product and preffered by the most consumers are chocolate and sweet bread, and the packaging of that product was very neat.The price offered is in accordance with what was expected by the consumer, and the price is quite affecting consumers to buy that product. The place used was strategic and the sheer number of existing outlets was enough, as well as the look and features of the points of saler was very interesting. The promotion was held in some varieties way, with a media campaign brochures that make consumers know BreadTalk, made them interested for buying the product, however, promotion had not been efficient, it was just efficient for the promotion of the product should been increded by giving discount on productâ€™s price